Recent Advances and Appropriate Use of Niosomes for the Treatment of Skin Cancer - Shinu, Pottathil; Nair, Anroop B; Kumari, Beena; Jacob, Shery; Kumar, Manish; Tiwari, Abhishek; Tiwari, Varsha; Venugopala, Katharigatta N; Attimarad, Mahesh; Nagaraja, Sreeharsha (Indian Journal of Pharmaceutical Education and Research, 2022)
Both melanoma and non-melanoma are the most common types of skin cancers affecting various populations across the globe. Skin malignancy is more prevalent among Caucasian populations. Non-melanoma types of skin cancers are further classified as basal cell and squamous cell carcinomas, respectively. The incidence of non-melanoma type of cancers is relatively higher than melanoma type of skin cancers. Recently published data shows that melanoma of the skin stands as the seventeenth most common type of cancer across the world. Niosome is a drug carrier in a novel drug delivery system wherein the drug is enclosed within the vesicle, which is made up of non-ionic surfactants that are stabilized by the addition of cholesterol. Niosomes help to overcome certain difficulties of skin drug deliveries such as insolubility, instability, low bioavailability, and fast debasement of medications. This review article mainly focuses on the use of niosomes in dermatology particularly aiming at the delivery of drugs via skin. In addition, this review discusses the specific use of niosomal drug delivery systems that may be useful in clinics. The niosomes are gaining popularity in the field of topical drug delivery due to their excellent characteristics like proficiency to carry both hydrophilic and lipophilic drugs, increasing the penetration of drugs, and enhancing drug stability and drug release at sustained levels.
Keywords: Niosomes; Drug carrier; Skin cancer; Penetration enhancer; Dosage form; Drug delivery; Drug therapy; Cancer treatment